Spontaneous Surface Flattening via Layer-by-Layer Assembly of Interdiffusing Polyelectrolyte Multilayers - Kim, Young Hun; Lee, Yong Man; Park, Juhyun; Ko, Min Jae; Park, Jong Hyeok; Jung, Woncheol; Yoo, Pil J. (AMER CHEMICAL SOC, 2010)
We report a facile means to achieve planarization of nonflat or patterned surfaces by utilizing the layer-by-layer (LbL) assembly of highly diffusive polyelectrolytes. The polyelectrolyte pair of linear polyethylenimine (LPEI) and poly(acrylic acid) (PAA) is known to maintain intrinsic diffusive mobility atop or even inside ionically complexed films prepared by LbL deposition. Under highly hydrated and swollen conditions during the sequential film buildup process, the LbL-assembled him of LPEI/PAA undergoes a topological self-deformation for minimizing surface area to satisfy the minimum-energy state or the surface, which eventually induces surface planarization along with spontaneous filling of surface textures or nonflat structures. This result is clearly different from other cases of applying nondiffusive polyelectrolytes onto patterned surfaces or confined structures, wherein surface roughening or incomplete filling is developed with the LbL assembly. Therefore, the approach proposed in this study can readily allow for surface planarization with the deposition of a relatively thin layer or polyelectrolyte multilayers. In addition. this strategy of planarization was extended to the surface modification of indium tin oxide (ITO) substrate. where surface smoothing and enhanced optical transmittance were obtained without sacrificing the electronic conductivity. Furthermore. we investigated the potential applicability or surface-treated ITO substrates as photoelectrodes or dye-sensitized solar cells prepared at room temperature. As a result, an enhanced photoconversion efficiency and improved device characteristics were obtained because of the synergistic role of polyelectrolyte deposition in improving the optical properties and acting as a blocking layer to prevent electron recombination with the electrolytes.
Keywords: SENSITIZED SOLAR-CELLS; EXPONENTIAL-GROWTH; TIO2 FILMS; FLUORESCENCE RECOVERY; WEAK POLYELECTROLYTES; OPTICAL-PROPERTIES; THIN-FILMS; ADSORPTION; DIFFUSION; MEMBRANES